India’s Space Technology: A New Alternative for Soft Power (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The future outlook for space activities in the 21st century depends on decisions taken by political leadership on Earth regarding how a country uses space science and technology to embed its national interest in its foreign policy. The Indian space program, which was established to facilitate the country's civilian socio-economic growth, is also observed in this perspective. And India is now among the few spacefaring countries of the 21st century as a consequence of its space entry in the 1960s and its technological prowess. By giving developed, developing, and impoverished nations access to space facilities, India is currently elevating its standing in international politics and relations. It essentially means that India now has a new Alternative for soft power in the form of the space industry. Availability of space services has become one of the basic needs of the nations in today's globalized world and engagement with the global community is essential for this sector to reach equal utility, hence India has developed it as an invaluable instrument of foreign policy by keeping space sector transactions open to the global community. Thus, this paper will explore India's contemporary space technology investment and its emergence as a new alternative of soft power resource by connecting with the theoretical side of soft power.